2011
DOI: 10.1093/nar/gkr1064
|View full text |Cite
|
Sign up to set email alerts
|

ELM--the database of eukaryotic linear motifs

Abstract: Linear motifs are short, evolutionarily plastic components of regulatory proteins and provide low-affinity interaction interfaces. These compact modules play central roles in mediating every aspect of the regulatory functionality of the cell. They are particularly prominent in mediating cell signaling, controlling protein turnover and directing protein localization. Given their importance, our understanding of motifs is surprisingly limited, largely as a result of the difficulty of discovery, both experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
323
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(329 citation statements)
references
References 42 publications
(48 reference statements)
3
323
0
3
Order By: Relevance
“…3A to F, 4B, and 6C to F). The results suggest that (10,8,18,21,25,11,18, and 26 cells for the columns going from left to right, respectively), and the ratio of the MFI in the nucleus to the MFI in the total cell was determined and expressed as a percentage (mean Ϯ standard deviation). (K to Q) Subcellular localization of FIV MA-CFP, CA-CFP, and NCp2-CFP.…”
Section: Discussionmentioning
confidence: 96%
“…3A to F, 4B, and 6C to F). The results suggest that (10,8,18,21,25,11,18, and 26 cells for the columns going from left to right, respectively), and the ratio of the MFI in the nucleus to the MFI in the total cell was determined and expressed as a percentage (mean Ϯ standard deviation). (K to Q) Subcellular localization of FIV MA-CFP, CA-CFP, and NCp2-CFP.…”
Section: Discussionmentioning
confidence: 96%
“…Sequence homology of Bud13p to ligands that bind to U2AF-homology motifs of RRM domains suggested that Bud13p interacts with Snu17p according to canonical UHM-ULM interactions (Fig. 6b,d) 13,15,16,[18][19][20][21][22] . However, the three-dimensional structure of the RES core complex demonstrated a distinct interaction mode unlike that of UHM and ULM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1a and 2b). In canonical UHM-ULM interactions, the ULM is formed by a positively charged sequence followed by an essential tryptophan [18][19][20][21][22] . In Bud13p the tryptophan is located at position 232, and it was supposed to bind to the hydrophobic pocket between α-helices 1 and 2 (refs.…”
Section: Structure Of the Res Core Complexmentioning
confidence: 99%
“…We identified 22 directed and 121 undirected interactions based on domain-motif and domain-domain interaction predictions, respectively. These interactions were found probable and highly-confident by the ELM structure filter [21] or by the PRINCESS PPI-evaluation tool [22], respectively. For the PRINCESS evaluation we defined a very stringent confidence value at 1000 to filter the total 1427 predicted PPIs to 121 highly-confident interactions.…”
Section: The Nrf2 Interactomementioning
confidence: 99%